Income and Welfare Analysis of Floating Net Cage Fish Farmers at Cirata Reservoir - Khansa Banafsaj; Ine Maulina; Atikah Nurhayati; Iwang Gumilar (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Floating Net Cage (FNC) aquaculture in the Jangari area of Cirata Reservoir serves as a primary household income source, necessitating examination of income levels, welfare levels, and the relationship between the two. This study aimed to analyze household income, welfare, and their relationship among FNC fish farmers in the Jangari area. The research was conducted from May to July 2026 using a case study method with a quantitative descriptive approach involving 30 respondents. Primary data were collected through observation and structured interviews, while secondary data were obtained from relevant institutions. Income was analyzed through revenue, production costs, and net income calculations. Household welfare was assessed using the 2014 BPS SUSENAS indicators covering income, expenditure, housing, education, health, and access to information technology. Results showed that average household income exceeded the Cianjur Regency minimum wage, indicating a high-income category. Welfare was predominantly high, with 93.33% of households classified as high welfare and 6.67% as moderate welfare. Spearman's rank correlation yielded a coefficient of 0.245 with a significance value of 0.191, indicating a positive but weak and statistically insignificant relationship between income and welfare.